2018
DOI: 10.1007/s11162-018-9526-y
|View full text |Cite
|
Sign up to set email alerts
|

Public Tuition on the Rise: Estimating the Effects of Louisiana’s Performance-Based Funding Policy on Institutional Tuition Levels

Abstract: Louisiana's performance-based funding (PBF) policy is one of the most recent implementations of performance funding established by a state for accountability purposes. Instead of examining direct academic outcomes, this study focuses on tuition increase as an (un) intended outcome of PBF implementation. We use data from multiple sources to create a panel dataset of public postsecondary institutions across the United States from 2005 to 2013. Applying Difference-in-Differences and propensity score analyses proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 78 publications
0
7
0
1
Order By: Relevance
“…Additional research on Indiana using a similar DD approach found that PBF was associated with increases in selectivity and decreases in underrepresented student enrollment at public 4-year institutions (Birdsall, 2018). Hu and Villarreal (2018) examined the impact of PBF adoption on tuition levels at public colleges and universities in Louisiana. The authors found that PBF implementation led to increases in tuition at public community colleges and in-state tuition at public 4-year institutions, which has the potential to restrict access to higher education for price-sensitive, lower-income students.…”
Section: The Unintended Consequences Of Pbf Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional research on Indiana using a similar DD approach found that PBF was associated with increases in selectivity and decreases in underrepresented student enrollment at public 4-year institutions (Birdsall, 2018). Hu and Villarreal (2018) examined the impact of PBF adoption on tuition levels at public colleges and universities in Louisiana. The authors found that PBF implementation led to increases in tuition at public community colleges and in-state tuition at public 4-year institutions, which has the potential to restrict access to higher education for price-sensitive, lower-income students.…”
Section: The Unintended Consequences Of Pbf Adoptionmentioning
confidence: 99%
“…PBF colleges that serve a disproportionate number of low-income students produced fewer associate degrees. Hu and Villarreal (2018) Difference-in-differences and propensity matching of public institutions using panel data, 2005-2013.…”
Section: (Continued)mentioning
confidence: 99%
“…The following recent studies have explored how PF policies are associated with institution-level finances, such as tuition levels and revenue sources. Hu and Villarreal ( 2019 ) examined Louisiana, which is unique in that while the state legislature sets tuition levels for 2- and 4-year sectors, the PF policy (GRAD Act) allows institutions to increase their own tuition levels up to a cap of between 5% and 10%, if these institutions meet performance targets. The GRAD Act outlines target areas (degree outcomes, transfer, workforce, and economic development), although each institution gets to determine its own annual target levels (Hu and Villarreal 2019 ).…”
Section: Policy Evaluationmentioning
confidence: 99%
“…Using DD on data from 2005 to 2013, Hu and Villarreal ( 2019 ) compared the tuition rates of 2- and 4-year institutions in Louisiana to three control groups: institutions in non-PF states nationally; institutions in non-PF states belonging to the Southern Regional Education Board; and institutions nationally in non-PF states that held tuition-setting authority. Results from the study showed that among 2-year colleges in Louisiana, tuition and fee levels increased significantly higher after PF, compared to institutions in each of the three control groups (Hu and Villarreal 2019 ). Propensity score matching confirmed the results that 2-year publics increased their tuition and fees at higher rates compared to counterfactual institutions not providing similar tuition increase mechanisms.…”
Section: Policy Evaluationmentioning
confidence: 99%
See 1 more Smart Citation